Superalloys 2008 (Eleventh International Symposium) 2008
DOI: 10.7449/2008/superalloys_2008_891_900
|View full text |Cite
|
Sign up to set email alerts
|

Atom Probe Tomography Analysis of Possible Rhenium Clustering in Nickel-Based Superalloys

Abstract: A local electrode atom probe is used to characterise a number of binary and commercial nickel-based alloys, specifically to determine whether rhenium atoms form solute clusters in these materials. The data are analysed via a statistical approach and results are compared to simulations which take the typical efficiency of the atom probe and the scatter in atomic positions into account. Thus, even the smallest clusters can -in principle -be detected by the algorithm. The analysis demonstrates conclusively that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…No clusters were detected. The same approach was adopted to study the distribution of Re in the γ phase of CMSX-4 where, similarly to the binary alloys, clusters were not found [24,25]. A sensitivity analysis of the approach on simulated 3DAP datesets revealed that sparse clusters (3.5 · 10 24 m −3 ) with 1 nm diameter should be evident, even when considering the detection efficiency and spatial resolution of the tool [24,25].…”
Section: Three-dimensional Atom Probementioning
confidence: 99%
See 3 more Smart Citations
“…No clusters were detected. The same approach was adopted to study the distribution of Re in the γ phase of CMSX-4 where, similarly to the binary alloys, clusters were not found [24,25]. A sensitivity analysis of the approach on simulated 3DAP datesets revealed that sparse clusters (3.5 · 10 24 m −3 ) with 1 nm diameter should be evident, even when considering the detection efficiency and spatial resolution of the tool [24,25].…”
Section: Three-dimensional Atom Probementioning
confidence: 99%
“…A maximum-separation friends-offriends algorithm was used to evaluate the presence of Re clusters in the data. The results were compared to simulated atom probe datasets [24] and randomised versions of themselves [25] (see Fig. 4).…”
Section: Three-dimensional Atom Probementioning
confidence: 99%
See 2 more Smart Citations
“…A ladder diagram is a cumulative presentation of solute content along a one-dimensional line, plotting the number of solute atoms encountered as a function of the total number of atoms encountered. Such ladder diagrams have been extensively used for identifying different phases as well as clustering in APTdata [23,53,54]. The slopes of these ladder diagrams are indicated inFigure 5, and represent the local concentration; in every case there is a clear signal of Mn segregation at the grain boundary, and the amount of grain boundary segregation ranges from 3 to 6 at.% higher than the composition in the neighboring grains.To get better statistics on the grain boundary and grain compositions, we constructed and analyzed 180 ladder diagrams such as those ofFigure 5, to assemble composition distributions unique to the boundary or the grains.…”
mentioning
confidence: 99%